Oracle self-service applications - Cameron, Melanie Anjele (New York McGraw-Hill Osborne Media, 2010)
"Get complete coverage of Oracle E-Business Suite's Self-Service modules, including Oracle iProcurement, Oracle Internet Expenses, Oracle iSupplier Portal, and Oracle iReceivables, inside this Oracle Press guide. Oracle Self-Service Applications discusses the features of each module and how they benefit organizational workflow, and reviews common implementation considerations that apply to all the modules. The book also provides detailed configuration instructions explaining each screen and field"--
Machine generated contents note: Chapter 1. Role of Self Service Modules in an Organization; -- Chapter 2. Implementation Considerations; -- Chapter 3. iProcurement Setup; -- Chapter 4. Using iProcurement; -- Chapter 5. iProcurement Processing; -- Chapter 6. iSupplier Setups; -- Chapter 7. iSupplier Processing; -- Chapter 8. iExpense Setups; -- Chapter 9. iExpense Processing; -- Chapter 10. iReceivables Setups; -- Chapter 11. iReceivables Processing
2
Keywords: Oracle E-business suite; Accounting -- Data processing; Electronic commerce -- Computer programs